2021
DOI: 10.1080/2162402x.2021.1928365
|View full text |Cite
|
Sign up to set email alerts
|

Genomic complexity is associated with epigenetic regulator mutations and poor prognosis in diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common type of lymphoma with high mutation burdens but a low response rate to immune checkpoint inhibitors. In this study, we performed targeted next-generation sequencing and fluorescent multiplex immunohistochemistry, and investigated the clinical significance and immunological effect of mutation numbers in 424 DLBCL patients treated with standard immunochemotherapy. We found that KMT2D and TP53 nonsynonymous mutations (MUT) were significantly associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…The poorer survival of EZB (but not MCD) genetic subtype among DhE patients in our cohort and A53/unsubtyped cases among DpE patients in the BCCA cohort was mostly attributable to cases with KMT2D mutations. KMT2D mutations (and EZB, P = 0.0027) were associated with decreased T cells in overall DLBCL with wild-type TP53 (35) but not in DhE cases; KMT2D mutations (and ST2/EZB/MCD subtypes) were significantly associated with higher numbers of mutated genes in DhE (P < 0.0001, data not shown) as in overall DLBCL (35). In solid tumor models, KMT2D and KMT2C are components of a p53 coactivator complex which is required for H3K4trimethylation and expression of p53-target genes in response to doxorubicin treatment (49).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The poorer survival of EZB (but not MCD) genetic subtype among DhE patients in our cohort and A53/unsubtyped cases among DpE patients in the BCCA cohort was mostly attributable to cases with KMT2D mutations. KMT2D mutations (and EZB, P = 0.0027) were associated with decreased T cells in overall DLBCL with wild-type TP53 (35) but not in DhE cases; KMT2D mutations (and ST2/EZB/MCD subtypes) were significantly associated with higher numbers of mutated genes in DhE (P < 0.0001, data not shown) as in overall DLBCL (35). In solid tumor models, KMT2D and KMT2C are components of a p53 coactivator complex which is required for H3K4trimethylation and expression of p53-target genes in response to doxorubicin treatment (49).…”
Section: Discussionmentioning
confidence: 94%
“…Sequencing was performed on an Illumina NextSeq 550 System platform. Most cases were sequenced with a 275-gene NGS panel (35) which was expanded to 315 genes (Supplementary Table S1) for 30 cases. The DNA fragments were ligated at their 5' ends with a sequencing platform-specific adapter containing unique molecular markers and sample index.…”
Section: Targeted Ngs and Genetic Alteration Analysismentioning
confidence: 99%
“…KMT2D LOF mutations are associated with altered immune signatures in DLBCL. In a recent study by You et al, KMT2D non-synonymous mutations have been shown to correlate with an overall increase in mutational burden in DLBCL, which intriguingly corresponded with low intra-tumoral T-cell infiltration in GCB DLBCL patients with WT P53 (You et al, 2021). Similarly, in solid cancers, KMT2D LOF mutations have been recently found to contribute to DNA damage, increased mutational burden and activation of transposable elements, which in this setting are associated with increased infiltration of effector immune cells, such as CD8 T cells, NK cells and M1 macrophages and decreased infiltration of Tregs and immature macrophages and better response to ICB activity (Wang et al, 2020;Liu et al, 2021).…”
Section: Kmt2dmentioning
confidence: 89%
“…Key new findings implicate DNA methylation heterogeneity as a core feature of DLBCL underlining the role of epigenetic dysfunction on lymphomagenesis [ 20 , 21 , 22 , 26 , 564 , 565 , 566 , 567 ]. Current findings highlight the potential role of miRs (lymphomiRs) as important factors in lymphomagenesis [ 568 ].…”
Section: Discussionmentioning
confidence: 99%